2013
DOI: 10.1212/wnl.0b013e3182a8418b
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical AD predicts decline in memory and executive functions in subjective complaints

Abstract: CSF evidence of preclinical AD in patients with subjective complaints predicted cognitive decline over time, encompassing more than memory alone. Executive functioning and global cognitive functioning also deteriorated. On the other hand, 2-year prognosis for patients without evidence of AD pathophysiology was good.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
101
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 33 publications
(33 reference statements)
18
101
2
1
Order By: Relevance
“…A study by van Harten et al (2013) found that CSF biomarker evidence of preclinical AD in patients with SCI predicted cognitive decline over time. No CSF or imaging biomarkers were available in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A study by van Harten et al (2013) found that CSF biomarker evidence of preclinical AD in patients with SCI predicted cognitive decline over time. No CSF or imaging biomarkers were available in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Different methods were used to classify the participants in these studies (see Supplementary Table online). Some studies used imaging alone, 1,811 others CSF biomarkers alone, 1214 others CSF biomarkers combined with imaging. 15 The proportion of individuals with SNAP among clinically normal participants aged >65 years was very consistent across these studies, many of which, perhaps coincidently, reported exactly 23% (see Supplementary Table online).…”
Section: Clinically Normal Individualsmentioning
confidence: 99%
“…The subsequent decline may ultimately meet diagnostic criteria for mild cognitive impairment or dementia, and risk of such progression may be increased among carriers of the apolipoprotein E (APOE) ε4 allele 1 and those with biomarker evidence supporting the diagnosis of Alzheimer’s disease (AD). 2 …”
Section: Introductionmentioning
confidence: 99%